Supramolecular synthesis of some molecular adducts of 4,4 `-bipyridine N,N `-dioxide - Arora, Kapildev K.; Talwelkar, Mayura S.; Pedireddi, V. R. (New Journal of Chemistry, 2009)
Molecular adducts (1a-1e) of 4,4'-bipyridine N,N'-dioxide, 1, respectively with cyanuric acid, trithiocyanuric acid, 1,3,5-trihydroxybenzene ( phloroglucinol), 1,3-dihydroxybenzene ( resorcinol) and 1,2,4,5-benzenetetracarboxylic acid have been reported. The major interactions observed in the structures 1a-1e are N-H center dot center dot center dot O, N-H center dot center dot center dot S, O-H center dot center dot center dot O and C-H center dot center dot center dot O, in the form of homomeric and heteromeric patterns of the constituents, either as a single or cyclic hydrogen-bonded motifs. While in the adduct 1a, both homomeric and heteromeric units of both the constituents were observed, no heteromeric interactions were observed in 1b and 1c. In addition, in 1b, homomeric aggregation of molecules of 1 occurred in association with water molecules. However, while heteromeric interactions prevail between the constituents in 1d and 1e, only one of the co-crystallizing species gave homomeric interactions (4,4'-bipyridine N,N'-dioxide in 1d; 1,2,4,5-benzenetetracarboxylic acid in 1e). Further, in either type of the patterns, the cyclic motifs are formed as a pair-wise hydrogen bonds comprising of strong and weak hydrogen bonds (N-H center dot center dot center dot O/C-H center dot center dot center dot O or O-H center dot center dot center dot O/C-H center dot center dot center dot O). In three-dimensions, the ensembles of molecules yield planar sheets, ladders and pseudorotaxane type assemblies.